Leishmania infantum Defective in Lipophosphoglycan Biosynthesis Interferes With Activation of Human Neutrophils - Quintela-Carvalho, Graziele; Goicochea, Astrid Madeleine Calero; Mançur-Santos, Vanessa; Viana, Sayonara de Melo; Luz, Yasmin da Silva; Dias, Beatriz Rocha Simões; Lázaro-Souza, Milena; Suarez, Martha; de Oliveira, Camila Indiani; Saraiva, Elvira M.; Brodskyn, Cláudia I.; Veras, Patrícia T.; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Visceral Leishmaniasis (VL) is often associated with hematologic manifestations that may interfere with neutrophil response. Lipophosphoglycan (LPG) is a major molecule on the surface of Leishmania promastigotes, which has been associated with several aspects of the parasite-vector-host interplay. Here, we investigated how LPG from Leishmania (L.) infantum, the principal etiological agent of visceral leishmaniasis in the New World, influences the initial establishment of infection during interaction with human neutrophils in an experimental setting in vitro. Human neutrophils obtained from peripheral blood samples were infected with either the wild type L. infantum (WT) strain or LPG-deficient mutant (∆lpg1). In this setting, ∆lpg1 parasites displayed reduced viability compared to WT L. infantum; such finding was reverted in the complemented ∆lpg1+LPG1 parasites at 3- and 6-hours post-infection. Confocal microscopy experiments indicated that this decreased survival was related to enhanced lysosomal fusion. In fact, LPG-deficient L. infantum parasites more frequently died inside neutrophil acidic compartments; a phenomenon that was reverted when host cells were treated with Wortmannin. We also observed an increase in the secretion of the neutrophil collagenase matrix metalloproteinase-8 (MMP-8) by cells infected with ∆lpg1 L. infantum compared to those which were infected with WT parasites. Furthermore, collagen I matrix degradation was found to be significantly increased in ∆lpg1 parasites-infected cells but not in WT-infected controls. Flow cytometry analysis revealed a substantial boost in production of reactive oxygen species (ROS) during infection with either WT or ∆lpg1 L. infantum. In addition, killing of ∆lpg1 parasites was shown to be more dependent on the ROS production than that of WT L. infantum. Of note, inhibition of the oxidative stress with Apocynin potentially fueled ∆lpg1 L. infantum fitness as it increased the intracellular parasite viability. Thus, our observations demonstrate that LPG may be a critical molecule fostering parasite survival in human neutrophils through a mechanism that involves cellular activation and generation of free radicals.